Microplastics in Rivers of South America: An Emerging Area of Research - Gamboa, Adriana Carolina; Gaida, William; Volpi, Gabriel Baraldi; Deitos, Tandara; Machado, Andressa Maiara de Almeida; Breunig, Fábio Marcelo; da Rosa, Genésio Mario; Flach, Kauane Andressa (Sociedade & Natureza, 2025)
Plastic pollution has emerged as one of our most pervasive and pressing environmental issues, impacting ecosystems, wildlife, and even human health globally. Microplastic research has primarily focused on oceans, whether in water, sediments, or organisms, generating a significant gap in understanding their presence and impact on other environments like rivers, which is a concern worldwide, and of paramount importance for us in Latin America and the Caribbean. To address this situation, we examined the current research on microplastics in South American rivers by conducting a Google Scholar search with keywords and Boolean operators, which allowed us to recover a series of articles related to this topic. We reviewed 49 articles published in 2023 to know methods for collecting and analyzing river samples. Our findings revealed limited information on microplastics in South America, with data only from Argentina, Brazil, Colombia, Ecuador, Paraguay, and Peru. Additionally, we found considerable variations in sample collection and analysis methods, hindering study comparisons. Bridging this knowledge gap is crucial for comprehending the extent of plastic pollution in the region. Since rivers are major microplastic contributors to oceans, this research will significantly aid in environmental protection efforts, emphasizing the global relevance of addressing riverine plastic pollution.